Understanding University Students' Perceptions and Attributions in Linguistically Diverse Mathematics Classrooms - Zhao, Yutao (Université d'Ottawa / University of Ottawa, 2024)
In recent years, the number of multilingual international students in Canadian university mathematics classrooms is on the rise, and a substantial body of literature has emerged on the topic of language diversity in mathematics education (e.g., Barwell et al., 2019; Chronaki & Planas, 2018; Suh, 2020; Tai, 2021). Whilst much research has been carried out in linguistically diverse settings, no single study exists which explores students' social perceptions of their peers in linguistically diverse mathematics classrooms. In addition, there is scant research conducted in post-secondary classrooms. The primary objective of the study is to fill the research gap by examining the factors that university students consider significant in their mathematics learning and exploring how students attribute both their own and others' successes and failures during mathematical discussions in linguistically diverse university classrooms. The study recruited nine participants from diverse linguistic backgrounds who have or were currently studying mathematics at the postsecondary level. Data collection was conducted through the utilization of group discussion, focus group interviews, and semi-structured interviews. This research contributes to a deeper understanding of university students' experiences in linguistically diverse mathematics classrooms and promotes university internationalization and positive student experiences.
Keywords: mathematics education; language diversity; higher education